Ribosomes from an Oxazolidinone-Resistant Mutant Confer Resistance to Eperezolid in a Staphylococcus aureus Cell-Free Transcription-Translation Assay - Murray, Robert W. (American Society for Microbiology, 1998)
Oxazolidinone-resistant mutants of Staphylococcus aureus, isolated with a spiral plating technique, had a 16-fold higher MIC (2 versus 32 μg/ml) of eperezolid when compared to the parental sensitive strain. Eperezolid inhibited in vitro protein translation with 50% inhibitory concentrations of 30 μM for the oxazolidinone-sensitive S30 extract and 75 μM for the resistant extract. Experiments mixing various combinations of S100 and crude ribosome preparations from oxazolidinone-sensitive and -resistant S. aureus strains in a transcription-translation assay demonstrated that the resistant determinant resided within the ribosomal fraction. Ribosomes from the oxazolidinone-resistant strain bound less drug than ribosomes from the sensitive strain, indicating that the ribosome is the site of action for the oxazolidinones. These experiments demonstrate that an alteration of the ribosome is responsible for some or all of the oxazolidinone resistance observed in the S. aureus mutant.